From motorcycle taxi to private bikes: how distraction and riding behavior influence traffic incidents in greater jakarta - Puspasari, Maya Arlini; Sanjaya, Beryl Putra; Hanowski, Richard J.; Iridiastadi, Hardianto; Arista, Salsabila Annisa; Nurkamila, Hasna Hamida; Putri Pribadyo, Claresta Yasmine; Ghanny, Ahmad; Junistya, Keishandra Nabila (Frontiers in Future Transportation, 2026)
Urban transport research encompasses transport safety, as accident-related fatalities are a significant problem, particularly in developing countries. In Indonesia, motorcycle crashes account for over 70% of all vehicle crashes. These crashes primarily result from behavioral and performance factors associated with the drivers of other vehicles. Most studies on motorcycle riders focus mainly on riding behavior and skills. However, few have examined how distractions influence rider behavior and traffic incidents, particularly when comparing private riders with motorcycle taxi riders. This study aims to develop a model for motorcycle riders by examining the causal relationships between variables through partial least squares structural equation modeling (PLS-SEM). This study also compares differences in driving behavior among age groups, genders, and driver types (private riders and motorcycle taxi riders). The results show that distractions significantly increase both errors and incidents, while risk perception directly influences speeding behavior. Riding errors and the use of protective equipment also make significant contributions to incident occurrence. Chi-square analyses further reveal that male and older riders report more consistent use of protective gear, younger riders exhibit higher levels of speeding and distraction, and taxi riders adopt safer practices compared to private riders. Based on these findings, this study proposes targeted safety strategies that include strengthening rule enforcement, implementing technological systems, conducting regular infrastructure inspections, and promoting public safety campaigns to enhance rider safety.